Psychological Distress and Stressful Life Events in Pediatric Complex Regional Pain Syndrome - Julia Wager; Hannah Brehmer; Gerrit Hirschfeld; Boris Zernikow (Pain Research and Management)
BACKGROUND: There is little knowledge regarding the association between psychological factors and complex regional pain syndrome (CRPS) in children. Specifically, it is not known which factors precipitate CRPS and which result from the ongoing painful disease.